Understanding stream incision, riparian function, and Indigenous knowledge to evaluate land management on the Prairie Band Potawatomi Nation - Mehl, Heidi Elizabeth (Kansas State University, 2018)
One of the critical challenges facing our world today, is managing our intensive use of land to support a growing population, while also ensuring the continued provision of ecosystem services that have supported human civilization thus far. The Great Plains region is representative of this complex global challenge because it supports some of the most productive agriculture in the world, yet is also degraded by land cover change, habitat loss, and nonpoint source pollution from nutrients, sediment, and pesticides. In the absence of regulatory remedies, nonpoint source pollution is typically addressed through voluntary adoption of Best Management Practices (BMPs). However, meaningful reductions in nonpoint source pollutants are too often elusive. This is due to two overarching factors: variable rates of effectiveness based on site-specific, geographic factors; and variable rates of adoption due to social, economic, and policy pressures. Therefore, to address the problem of nonpoint source pollution, we must better understand the interacting physical processes behind nonpoint source pollution, and the cultural processes driving land management choices. The unifying variable between rates of effectiveness and rates of adoption, is land use/land cover (LULC) driven by land management practices. This dissertation seeks to integrate an advanced understanding of the interactions between the physical impacts of LULC on nonpoint source pollution removal in stream riparian zones, with an evaluation of Indigenous cultural frameworks to better inform land management paradigms. This dissertation explores the relationship between fluvial geomorphology, hydrology, and nutrient dynamics in riparian areas of incised stream channels. To add to this understanding, I utilize a transect of nested piezometers to observe riparian zone hydrology under both forested and row-crop land cover along an incised stream, James Creek in northeast Kansas. The investigation of coupled hydrologic/biogeochemical relationships addresses whether precipitation interflow to incised channels is interacting with the soil in such a way that denitrification processes are facilitated, or inhibited. These issues may be better addressed through multiple BMPs and management for whole ecosystems – a view that is contained within the Traditional Ecological Knowledge (TEK) framework. Understanding Indigenous values and land management preferences may provide an alternative cultural framework for valuing native land cover, and help government agencies and NGOs promote increased adoption of BMPs. A greater understanding of these Indigenous cultural frameworks will also help to bridge gaps in understanding between government agencies and Indigenous tribes in questions of resource management. Therefore, this dissertation examines Indigenous governance of natural resources, and historical barriers that have led to the unique situations that exist today. Utilizing mixed-methods research, the overarching goal of this dissertation is to apply advanced understandings of riparian hydrology and water quality function in the Great Plains to best management practice recommendations based on a sound understanding of Indigenous nature-society value systems.
Keywords: Hydrology; fluvial geomorphology; nitrate; Indigenous knowledge; land management